Sexagon : Muslims, France and the sexualization of national culture - Mack, Mehammed Amadeus (Modern language initiative., 2017)
In contemporary France, particularly in the banlieues of Paris, the figure of the young, virile, hypermasculine Muslim looms large. So large, in fact, it often supersedes liberal secular society's understanding of gender and sexuality altogether. Engaging the nexus of race, gender, nation, and sexuality, Sexagon studies the broad politicization of Franco-Arab identity in the context of French culture and its assumptions about appropriate modes of sexual and gender expression, both gay and straight. Surveying representations of young Muslim men and women in literature, film, popular journalism, television, and erotica as well as in psychoanalysis, ethnography, and gay and lesbian activist rhetoric, Mehammed Amadeus Mack reveals the myriad ways in which communities of immigrant origin are continually and consistently scapegoated as already and always outside the boundary of French citizenship regardless of where the individuals within these communities were born. At the same time, through deft readings of--among other things--fashion photography and online hook-up sites, Mack shows how Franco-Arab youth culture is commodified and fetishized to the point of sexual fantasy.